ANALISIS PENGARUH CAPITAL ADEQUACY RATIO DAN LOAN-TODEPOSIT RATIO TERHADAP NON PERFORMING LOAN SEBELUM DAN SESUDAH PANDEMI COVID-19 (Studi Empiris Pada Bank Konvensional yang Terdaftar di OJK Periode 2018-2021) - Aisha Nur Azlia Dwiputri; R. Djoko Sampurno (Faculty of Economics and Business Diponegoro University, 2022)
This research aims to investigate the relationship between capital adequacy ratio (CAR) and loan-to-deposit-ratio (LDR) as the independent variables, and non-performing loan (NPL) as the dependent variable in Indonesian banks before and during the pandemic COVID-19. The sample data to be analysed is from 53 banks with 212 observations. The author uses a balanced panel data set for the four-year period regression model and unbalanced panel data sets for the non-crisis period and crisis period analyses. The author uses panel data regression to produce the study outcomes. Then the outcomes reveal that bank with higher loan-to-deposit ratio tend to be more susceptible to higher NPL. CAR exerts no significant effects on NPL. Those results are tested from the four-year-period data. When the global economy is not disturbed with COVID-19 pandemic, the two variables have insignificant and negative effects on NPL. The outcomes are studied based on the data from 2018-2019. Furthermore, when COVID-19 pandemic occurs, only CAR has a significant impact, which is negative, on NPL. This finding informs that regulator authorities can use capital regulation as an effective tool to mitigate risk resulted by non-performing loan in banks during a pandemic